Saturated Free Fatty Acids Induce Cholangiocyte Lipoapoptosis - Natarajan, Sathish Kumar (Hepatology, 2014)
Recent studies have identified a cholestatic variant of nonalcoholic fatty liver disease (NAFLD) with portal inflammation and ductular reaction. Based on reports of biliary damage, as well as increased circulating free fatty acids (FFAs) in NAFLD, we hypothesized the involvement of cholangiocyte lipoapoptosis as a mechanism of cellular injury. Here, we demonstrate that the saturated FFAs palmitate and stearate induced robust and rapid cell death in cholangiocytes. Palmitate and stearate induced cholangiocyte lipoapoptosis in a concentration-dependent manner in multiple cholangiocyte-derived cell lines. The mechanism of lipoapoptosis relied on the activation of caspase 3/7 activity. There was also a significant up-regulation of the proapoptotic BH3-containing protein, PUMA. In addition, palmitate-induced cholangiocyte lipoapoptosis involved a time-dependent increase in the nuclear localization of forkhead family of transcription factor 3 (FoxO3). We show evidence for posttranslational modification of FoxO3, including early (6 hours) deacetylation and dephosphorylation that coincide with localization of FoxO3 in the nuclear compartment. By 16 hours, nuclear FoxO3 is both phosphorylated and acetylated. Knockdown studies confirmed that FoxO3 and its downstream target, PUMA, were critical for palmitate- and stearate-induced cholangiocyte lipoapoptosis. Interestingly, cultured cholangiocyte-derived cells did not accumulate appreciable amounts of neutral lipid upon FFA treatment. CONCLUSION: Our data show that the saturated FFAs palmitate and stearate induced cholangiocyte lipoapoptosis by way of caspase activation, nuclear translocation of FoxO3, and increased proapoptotic PUMA expression. These results suggest that cholangiocyte injury may occur through lipoapoptosis in NAFLD and nonalcoholic steatohepatitis patients.